Epstein-Barr viral product-containing exosomes promote fibrosis and nasopharyngeal carcinoma progression through activation of YAP1/FAPα signaling in fibroblasts - Lee, Po-Ju; Sui, Yun-Hua; Liu, Tzu-Tung; Tsang, Ngan-Ming; Huang, Chen-Han; Lin, Ting-Yi; Chang, Kai-Ping; Liu, Shu-Chen (Journal of experimental & clinical cancer research, 2022)
Background The progression of nasopharyngeal carcinoma (NPC) is profoundly affected by Epstein-Barr virus (EBV) infection. However, the role of EBV in the intercommunication between NPC and surrounding stromal cells has yet to be explored. Methods NPC biopsies were obtained for immunohistochemical (IHC) analyses. Clinical correlations between the expression of active YAP1/FAPα and the fibrotic response and between YAP1/FAPα and the density of cytotoxic CD8a+ T lymphocytes were determined. Survival times based on IHC scores were compared between groups using Kaplan-Meier survival and log-rank tests. Independent prognostic factors for metastasis/recurrence-free survival and overall survival were identified using univariate and multivariate Cox regression models. Fibroblasts were isolated from human nasopharyngeal biopsies. Exosomes were purified from culture supernatants of EBV+-positive NPC cells. The effects of EBV product-containing exosomes on fibroblast activation, fibrotic response, tumor growth, immune response, and correlations between the expression of featured genes were investigated using gel contraction assays, ELISAs, EdU incorporation assays, real-time impedance assays, RNA sequencing, immunostaining, 3D cancer spheroid coculture systems, and an NPC xenograft model. Results NPC patients who developed metastasis had significantly higher levels of active YAP1 and FAPα in their tumor stroma, which was further correlated with tumor fibrosis and poorer metastasis-free survival. Exosomes released from EBV+-NPC cells contained abundant FAPα protein and EBV-encoded latent membrane protein 1. Viral product-containing exosomes markedly enhanced the fibrotic response and tumor growth in a mouse xenograft model. IHC analyses of human NPC and NPC xenografts revealed positive correlations between levels of active YAP1 and FAPα, YAP1 and the fibrotic response, and FAPα and the fibrotic response. Mechanistic studies showed that treatment of fibroblasts with viral product-containing exosomes promoted the characteristics of cancer-associated fibroblasts by stimulating YAP1 signaling and the production of the immunosuppressive cytokines IL8, CCL2, and IL6. Inhibition of YAP1 activation markedly reversed these exosome-mediated protumoral effects, resulting in reduced contractility, inactivation of YAP1 signaling, and decreased production of immunosuppressive cytokines in fibroblasts. Furthermore, fibroblasts stimulated with these viral product-containing exosomes promoted NPC resistance to T cell-mediated cytotoxicity within tumor spheroids. In NPC tissues, a significant negative correlation was found between YAP1/FAPα and the density of CD8a+ T lymphocytes with a granzyme B signature. Conclusion EBV orchestrates interactions with the host and surrounding stroma by stimulating the functions of YAP1 and FAPα in fibroblasts through exosome cargos to create a more immunosuppressive, proinvasive microenvironment.